2008
DOI: 10.1021/ja8023466
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (+)-Cortistatin A

Abstract: Cortistatin A is a marine steroid with highly selective and perhaps mechanistically unique antiangiogenic activity. Herein we report a synthesis of this natural product by way of “cortistatinone”, an intermediate ideally suited for investigating the key pharmacophore of the cortistatin family. The synthesis begins with a terrestrial steroid and traverses a route to cortistatin A through the discovery of unique chemical reactivity. Specifically, we demonstrate the first example of a directed, geminal C−H bisoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(93 citation statements)
references
References 23 publications
1
85
0
3
Order By: Relevance
“…Scheme 53) by Baran and co-workers. 391 This impressive reaction, which is the first example of an alcohol-directed geminal dibromination of an unactivated methyl group, delivered the product in 57% yield after trapping the alcohol with TMSCl to avoid ether formation (Scheme 83).…”
Section: Scheme 82mentioning
confidence: 99%
“…Scheme 53) by Baran and co-workers. 391 This impressive reaction, which is the first example of an alcohol-directed geminal dibromination of an unactivated methyl group, delivered the product in 57% yield after trapping the alcohol with TMSCl to avoid ether formation (Scheme 83).…”
Section: Scheme 82mentioning
confidence: 99%
“…[11] Their collective efforts, commencing from a broad array of starting materials and guided by an assortment of creative strategies, have culminated in one semi-synthesis, [12] three total syntheses, [13][14][15] and two formal syntheses, [16] as well as a number of syntheses of the pentacyclic cortistatin core and some illuminating model studies. [17] In an attempt to present this synthetic work in a comprehensive yet palatable manner, these approaches are organized herein by the method for B ring formation.…”
Section: Synthetic Approaches To the Cortistatinsmentioning
confidence: 99%
“…[12] Their semi-synthetic effort began with the commercially available steroid prednisone (14), which was converted into the formamide 15 in five steps and 26 % overall yield (Scheme 2). Mukaiyama hydration of alkene 15 with Co(acac) 2 and PhSiH 3 was then followed by orthoamide formation and subsequent cleavage of the acetate to deliver the secondary alcohol 16 in 65 % yield.…”
Section: Ring-expansion Approaches -Syntheses Of Cortistatin Amentioning
confidence: 99%
“…Unexpectedly, the undesired 5 0 -isomer was preferentially formed. A trial of the Stille coupling reaction between triflate 4 and 7-(trimethylstannyl)isoquinoline, as Baran has reported using the corresponding vinyl iodide instead of 4,4) resulted in the decomposition of both compounds. Hydrogenation of the 16,17-double bond of 8 proceeded stereoselectively on 10% Pd/C for 5 h to give 9.…”
Section: 9)mentioning
confidence: 99%
“…Thus, 1a could be a promising selective anti-angiogenic agent. The synthesis of 1a from the steroid, prednisone, has been achieved by Baran's group, 4) and several synthetic studies have been reported. 5,6) The structure-activity relationship studies of cortistatins 7) have revealed that a) introduction of an oxygen function on the D-ring diminishes the activity, b) the isoquinoline ring is crucial, and c) the dihydroxy group on the A-ring is removable.…”
mentioning
confidence: 99%